SISTEM INFORMASI MONITORING TRANSAKSI PADA KANTOR PERWAKILAN BANK INDONESIA PROVINSI LAMPUNG BERBASIS WEB - Dwi Sakethi; Yohana Tri Utami; Rangkas Andreansyah (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
The information system of transaction monitoring at the Representative Office of Bank Indonesia in the Lampung Province is a system that aims to provide features in accordance with the needs of related information systems such as managing transaction data, monitoring transaction files, and verifying transaction data. The system development process uses the extreme programming method, and in the system testing process uses black box testing and user acceptance tests. Initial data collection was carried out by conducting observations and interviews with Bank Indonesia employees in Lampung Province to obtain functional requirements related to user stories, and to obtain system acceptance criteria or user acceptance criteria. System functionality testing is carried out using the black box testing method, while system acceptance testing is carried out using the user acceptance test method. Based on the black box testing, and the user acceptance test, the entire functional system has been accepted, and can be used at the Bank Indonesia Representative Office, Lampung Province.